Ensuring Security Using Blockchain Technology - Padeli; Jawahir; Sholahudin Aprizal, Muhammad; Yaser Fadilla, Muhamad; Apriana Adha, Mochamad Rivaldi (Blockchain Frontier Technology, 2023)
The world is heading toward an era of digitization and automation, especially in the development of Blockchain technology. Blockchain in the Internet of Things network is an innovative approach that can make communication between such network devices distributed, autonomous and secure. Blockchain, in this context, is a set of cryptographically linked blocks. Transactions in the network act as the primary carrier of information about the state of the nodes, as well as output information from the nodes themselves for autonomous network functions. A node is a "smart" device, sensor, or microcontroller that connects a group of sensors. Blockchain will be used to provide secure data transmission and device processing on the Internet of Things network. This study discusses the main challenges of applying technology in distributed networks.